Proceedings of Integrated Intelligence Enable Networks and Computing IIENC 2020 - Singh Mer, Krishan Kant; Semwal, Vijay Bhaskar; Bijalwan, Vishwanath; Crespo, Rubén González (Algorithms for Intelligent Systems, 2021)
XVIII, 1004 p. 539 illus., 364 illus. in color.